PENGARUH KEPEMIMPINAN KEPALA SEKOLAH, IKLIM, SEKOLAH, DAN DISIPLIN KERJA GURU TERHADAP KINERJA GURU MI SWASTA KECAMATAN WARUNGASEM BATANG - Millatul Mustanida; Ghufron Abdullah; Rosalina Br Ginting (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Abstract: Problem Formulation 1) Is there a significant influence of the Principal's leadership on the performance of teachers in Private MI Warungasem District; 2) Is there a significant influence of school climate on teacher performance in Private MI Warungasem District; 3) Is there a significant influence of work discipline on teacher performance in Private MI Warungasem District; 4) Is there a significant influence of the principal's leadership, school climate, and work discipline on teacher performance in Private MI Warungasem District. This research uses a quantitative approach, located in Private MI in Warungasem sub-district. The data collection technique is by distributing questionnaires or questionnaires. The data analysis used was using simple correlation analysis and multiple regretion analysis with the help of the SPSS windows program The results of this study show that there is a significant influence of the principal's leadership on teacher performance which is stated by the statement Y= 86,187+0.095X_1. with a α < value of 0.50; Correlation Strength is 0.310. With a contribution of 9.6%. There is a significant influence of school climate on teacher performance which is stated by the statement Y = 105.034-0.113X_2 with a value of α = 0.50 correlation force of -0.113 with a contribution of 1.3%. There was a significant influence of teacher discipline on teacher performance which was stated by the statement Y = 84.456 + 0.103X_3. with a value of α = 0.50 the correlation force is 0.291 with a contribution of 9.6%. There is an influence of the principal's leadership, school climate, and teacher work discipline on teacher performance which is stated by the statement Y= 86.785 + 0.089X1 – 0.104X2 + 0.094X3; correlation strength of 0.763. With a contribution of 58.2%. The results of the study show that there is an influence between the principal's leadership, school climate, and teacher work discipline on teacher performance. Therefore, it is recommended that school principals always increase their potential in coaching teachers more openly, in addition to being able to coordinate between school residents so that the school climate is more conducive, and teacher discipline to be reconsidered so that teacher performance can be improved. Keywords: Teacher Performance, School Principal Leadership, School Climate, and Teacher Work Discipline